Парадокс Леонтьєва: використання в умовах повоєнної економки - Босак, А. О.; Bosak, A. O. (Видавництво Львівської політехніки, 2023)
Досліджено особливості використання парадоксу Леонтьєва в умовах повоєнного відновлення економіки України. Систематизовано результати емпіричних перевірок моделі Хекшера – Оліна в контексті різних причин недотримання її окремих умов. Узагальнено комбінації показників оцінювання параметрів факторів виробництва, перевірено їх релевантність щодо окремих завдань тестування факторів. Сформовано рекомендації щодо використання статистики Леонтьєва для розвитку міжнародної економічної діяльності України.

The Heckscher – Ohlin – Samuelson model provides a mathematical proof of the possibility of equalizing relative and absolute prices of production factors due to international trade, provided certain assumptions are met. Wassily Leontief proved, in practice these assumptions are not followed. Therefore, there is a need to adjust the parameters of the model in the calculations of indicators of value estimation and the use of production factors. The purpose of this research is to study the results of calculating the parameters of Leontief’s statistics and to identify their potential application in the conditions of post-war economic recovery of Ukraine. The main research methods were theoretical generalization, economic statistical analysis, and multivariate linear regression. During the research process, several partial tasks were completed, namely: 1) systematizing the results of empirical tests of the provisions of the Heckscher – Ohlin model in terms of explanations of the reasons for non-compliance with its individual conditions; 2) summarizing the combinations of indicators for the evaluation of parameters of production factors and verifying their relevance to individual tasks of factor testing; 3) formulating recommendations for the application of the Leontief’s statistics in the conditions of the post-war economic recovery of Ukraine. All partial explanations of the Leontief’s paradox can be used to modify the principles of calculating the indicators of production factors. Most often, there is a need to correct the following elements of statistical data: changes in the structure of the economy during the crisis period and as a result of military operations; taking into account the heterogeneity of labor and the need for financing education and training of specialists; different productivity of technologies used in the production of similar goods; the impact of the import tariff and its differentiation by product groups and geographical features; import of capital-intensive raw materials for production of labor-intensive products; use of various methods of factor intensity calculation. In addition to instrumental discrepancies and the imperfection of the calculation methodology, there is a problem with the very concept of representing the dependence of gross output on the structure of production factors. The classical Cobb-Douglas production function and its numerous modifications do not unambiguously solve the question of capital measurement. Moreover, the question of the primacy of the impact of consumption growth on output and the impact of output growth on consumption remains unresolved. The practical significance of the research lies in the fact that in the conditions of post-war economic recovery of Ukraine, most of the assumptions of the Heckscher – Ohlin model are nullified, as the state will have to introduce strict restrictions on the movement of production factors and international trade for some time. This will allow to form real statistics on the use of production factors and, on its basis, to carry out programming of Ukraine’s international trade. On the basis of the Heckscher – Ohlin theory and Leontief’s statistics, it is possible to develop economic-mathematical models of the optimal distribution and effective use of production factors among industries. Based on the results of such modeling, a set of measures to restore the demographic potential should be developed in three areas: stimulating re-emigration, creating conditions for increasing the birth rate, and intensifying efforts to attract foreign labor. Attracting foreign capital will be possible if a favorable investment and tax climate is successfully created, corruption is overcome, and judicial reform is implemented. And technologies will come following investments. After the initial stage of economic recovery, programs of macroeconomic programming should be reviewed with a mix of emphasis on optimization of monetary and credit policies. And finally, after the economy recovers to at least the prewar level, start creating conditions for the development of own technologies and reforming the education system.
The Leontief’s paradox: use in the conditions of the post-war economy
Keywords: теорія Хекшера – Оліна; парадокс Леонтьєва; фактори виробництва; капіталомісткість; працемісткість; відносні ціни факторів виробництва; вирівнювання цін на фактори виробництва; Heckscher – Ohlin theory; Leontief’s paradox; factors of production; capital intensity; labor intensity; relative factors prices; factor price equalization theorem (FPET); 330.111.4